The burden of zoonoses in Paraguay: A systematic review - Liz Paola Noguera Zayas; Simon Rüegg; Paul Torgerson (Public Library of Science (PLoS), 2021)
Introduction Underestimation of zoonoses is exacerbated in low and middle-income countries due mainly to inequalities with serious consequences in healthcare. This is difficult to gauge and reduce the impact of those diseases. Our study focuses on Paraguay, where the livestock industry is one of the major components of the country's economy. Therefore, the rationale of this study was to develop a case study in Paraguay to estimate the dual impact of zoonotic diseases on both the human health and animal health sector and thus determine the societal burden of such diseases. Methodology/Principal findings We conducted a systemic review (including a meta-analysis) to assess the burden of zoonoses in Paraguay, including official reports and grey literature of disease incidence and prevalence. We estimated the Disability Adjusted Life Years (DALYs) and Zoonosis Disability Adjusted Life Years (zDALYs) to measure the difference between the current health status and the desired health situation of animals and the Paraguayan population based on 50 zoonotic diseases suggested by the WHO (World Health Organization), OIE (World Organization for Animal Health) and the National Health in Paraguay. The total DALYs represent 19,384 (95% CI: from 15,805 to 29,733), and zDALYs, 62,178 (95% CI: from 48,696 to 77,188). According to the results, the priority pathogens for DALYs are E. coli, Trypanosoma cruzi, Leishmania spp, and Toxoplasma gondii. When we include the additional animal health burden, the most important pathogens are Brucella spp, E. coli, Trypanosoma cruzi, and Fasciola hepatica for zDALYs. Conclusion/Significance This is the first study to integrate DALYs and zDALYs with important clues related to the health status of Paraguay. Through DALYs and zDALYs, our perspective becomes more complete because we consider not only human health but also animal health. This is important for setting priorities in disease control, especially in a society where livestock contribute significantly to the economy and to human well-being. Author summary Zoonotic diseases in man are more likely to occur where there is a close association between man and animals. The control of zoonotic diseases requires a "One Health" approach to reduce the risk of such transmission. This represents a challenge in low and middle-income countries, due to inequalities and limited resources, especially in healthcare. For that reason, we need to quantify the impact of zoonoses in those countries such as Paraguay, a major exporter of beef and agricultural products, so that disease control priorities can be set. Through a systematic review, we estimate the Disability Adjusted Life Years (DALYs) and the Zoonosis Disability Adjusted Life Years (zDALYs) based on incidence and prevalence of zoonoses to find gaps between the real and the desired health status of both animals and humans in Paraguay. The zDALY ensures the total societal burden of disease, rather than just the direct human disease burden. We have through zDALYs a more equitable method for disease burden analysis that has a dual impact on human and animal health. Accordingly, we have found that those diseases with the highest zDALY are brucellosis, colibacillosis and Chagas disease.